Effect of two different colloid priming strategies in infants weighing less than 5 kg undergoing on‐pump cardiac surgeries. Issue 1 (7th October 2019) - Zhou, Chun; Tong, Yuanyuan; Feng, Zhengyi; Cui, Yongli; Zhao, Mingxia; Hu, Jinxiao; Liu, Kai; Zhao, Ju; Liu, Jinping
Abstract: Our aim was to explore the effect of two different priming strategies (artificial colloid only vs. artificial colloid combined with human serum albumin) on the prognosis of children weighing less than 5 kg undergoing on‐pump congenital heart disease (CHD) surgery. A total of 65 children weighing less than 5 kg who underwent on‐pump CHD surgery in our hospital from September 2016 to December 2017 were enrolled in this study. The children were randomly divided into two groups: artificial colloid priming group (AC group, n  = 33) and artificial colloid combined albumin priming group (ACA group, n  = 32). The primary clinical endpoint was the peri‐CPB colloid osmotic pressure (COP). Secondary clinical endpoints included perioperative blood product and hemostatic drug consumption, postoperative renal function, coagulation function, postoperative renal function, and postoperative recovery parameters. COP values were not significant in the priming system as well as peri‐CPB time points between the two groups ( P  > .05). Platelet consumption in the AC group was significantly lower than that in the ACA group ( P  < .05). There were no significant differences in the use of other blood products and hemostatic drugs as well as perioperative coagulation parameters between the two groups ( P  > .05). Postoperative length of stay in the AC group was significantly lower than that in the ACA group ( P  < .05). There were no significant differences in mortality, postoperative mechanical ventilation time, ICU time, and perioperative adverse events (including postoperative AKI) occurrences between the two groups ( P  > .05). In the on‐pump cardiac surgeries of patients weighing less than 5 kg, total colloidal priming would not affect peri‐CPB COP values, postoperative coagulation function, and blood products consumption. Total artificial colloidal priming strategy is feasible in low‐weight patients.